The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1530/eje.0.1470641
|View full text |Cite
|
Sign up to set email alerts
|

The risk of myocardial infarction is enhanced by a synergistic interaction between serum insulin and smoking

Abstract: Objectives: To evaluate the relationship between levels of serum insulin, the homeostasis model assessment (HOMA) and IGF-binding protein-1 (IGFBP-1) as factors related to myocardial infarction (MI) risk, and their interaction with lifestyle-related risk factors. Design: The Stockholm epidemiology programme (SHEEP), a case-control study, consisting of 749 first-time MI cases (510 men, 239 women) and 1101 healthy controls (705 men, 396 women) was used. Methods: The risk of developing MI was assessed by calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Separate analyses, however, showed that waist was significantly negatively correlated to IGFBP-1 in men. 51 A positive correlation between IGFBP-1 and total cholesterol was also found in women, which could be explained by the relationship to HDL cholesterol. 5,6,22,45 The most consistent finding concerning serum lipids was the positive correlation between IGFBP-1 and HDL-C in women.…”
Section: Igfbp-1 and Insulinmentioning
confidence: 93%
See 1 more Smart Citation
“…Separate analyses, however, showed that waist was significantly negatively correlated to IGFBP-1 in men. 51 A positive correlation between IGFBP-1 and total cholesterol was also found in women, which could be explained by the relationship to HDL cholesterol. 5,6,22,45 The most consistent finding concerning serum lipids was the positive correlation between IGFBP-1 and HDL-C in women.…”
Section: Igfbp-1 and Insulinmentioning
confidence: 93%
“…51 Identifying the extent and causes of sex differences in biochemical, physiological and social outcomes is necessary in understanding variability in susceptibility to a disease and its cause. Men have in general a more disadvantageous cardiovascular risk profile than women.…”
Section: Igfbp-1 and Cortisolmentioning
confidence: 99%
“…Total cholesterol, triglycerides and TNFα levels were determined from blood samples drawn by venous puncture undertaken during the health examination as previously described elsewhere [14,15]. Serum samples were stored at − 70°C until analyses for IGFBP-1 and insulin were performed.…”
Section: Methodsmentioning
confidence: 99%
“…167 Moreover, there may be a synergistic effect of cigarette smoking and insulin resistance in the development of atherosclerosis, suggesting a particularly important role in patients with diabetes mellitus. 168 Smoking cessation interventions should be pursued aggressively, for the benefits in patients with diabetes mellitus at least match those found in patients without diabetes mellitus. 169 A variety of smoking cessation interventions are available, including counseling, nicotine replacement therapy, antidepressants (buproprion), and the nicotine partial receptor agonist, varenicline.…”
Section: Smoking Cessationmentioning
confidence: 99%